Nautical radar clutter suppression and small target detection based on image spectrum filtering and Hough transform - Zhonghua Bao (The Journal of Engineering, 2019)
Here, a new clutter suppression and small target detection method was presented for nautical radars based on image spectrum filtering and Hough transform (HT). It is well known that sea clutter can be decomposed into texture component (TC) and spiky component (SC). First, the raw echo image was transferred to spectrum field, taking use of the narrow band feature of TC clutter in the image spectrum field, a 2D filter named as invert clutter response filter was designed to filter the energy of TC clutter in image spectrum field and then recovering the echo image. After that, a 2D CFAR detector was used to get a coarse detection report. Since the influence of the remaining SC clutter, quite a lot of false-alarmed detections may appear for the coarse detections. To solve this problem, the HT technique was proposed to extract real target track lines from many but distributed SC clutter caused false alarms. Measured and simulated results show that the proposed method is quite effective.